A Comparison of Exogenous Labels for the Histological Identification of Transplanted Neural Stem Cells. Issue 4 (April 2017) - Nicholls, Francesca J.; Liu, Jessie R.; Modo, Michel
The interpretation of cell transplantation experiments is often dependent on the presence of an exogenous label for the identification of implanted cells. The exogenous labels Hoechst 33342, 5-bromo-2′-deoxyuridine (BrdU), PKH26, and Qtracker were compared for their labeling efficiency, cellular effects, and reliability to identify a human neural stem cell (hNSC) line implanted intracerebrally into the rat brain. Hoechst 33342 (2 mg/ml) exhibited a delayed cytotoxicity that killed all cells within 7 days. This label was hence not progressed to in vivo studies. PKH26 (5 μM), Qtracker (15 nM), and BrdU (0.2 μM) labeled 100% of the cell population at day 1, although BrdU labeling declined by day 7. BrdU and Qtracker exerted effects on proliferation and differentiation. PKH26 reduced viability and proliferation at day 1, but this normalized by day 7. In an in vitro coculture assay, all labels transferred to unlabeled cells. After transplantation, the reliability of exogenous labels was assessed against the gold standard of a human-specific nuclear antigen (HNA) antibody. BrdU, PKH26, and Qtracker resulted in a very small proportion (<2%) of false positives, but a significant amount of false negatives (~30%), with little change between 1 and 7 days. Exogenous labels can therefore be reliable to identify transplanted cells without exerting major cellular effects, but validation is required. The interpretation of cell transplantation experiments should be presented in the context of the label's limitations.